PENGARUH LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA DI KANTOR CAMAT LUAHAGUNDRE MANIAMOLO KABUPATEN NIAS SELATAN - Safirdaus Dachi (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
This study aims to determine the effect of the work environment on work motivation in the Luahagundre Maniamolo Sub-district Office, South Nias Regency. This type of research is an associative quantitative research. The sample in this study amounted to 30 employees. The analytical method used in this research is simple linear regression analysis. The results of this study indicate that there is a significant influence between the work environment and work motivation in the Luahagundre Maniamolo Sub-district Office, South Nias Regency. In this study, a simple linear regression equation was obtained, namely: Y = 8.550 + 0.860X + 0.145 obtained tcount (5.919) > ttable (1.701) and a significant level of 0.000 <0.05. Then the decision is that Ha is accepted, H0 is rejected, meaning that the work environment variable has a positive and significant effect on work motivation. Then an R Square value of 0.556 or 55.6% is obtained. It can be concluded that the work environment has an influence on work motivation in the Luahagundre Maniamolo Sub-District Office, South Nias Regency